1995
DOI: 10.1161/01.str.26.9.1697
|View full text |Cite
|
Sign up to set email alerts
|

Thrombus Associated With Mitral Valve Calcification

Abstract: These cases support the hypothesis that thrombus formation may be a pathophysiological link between ischemic cerebral events and mitral annular calcification in some patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 17 publications
3
18
0
1
Order By: Relevance
“…MAC may act as a direct source of emboli or merely as a marker of conditions associated with thrombo-embolism, such as hypertension, general atherosclerosis, advanced age, congestive heart failure, atrial fibrillation and diabetes [1-3, [16][17][18][19][20][21]. Case reports and epidemiological studies suggest a strong relation between MAC and stroke [3, [22][23][24][25][26][27][28].…”
mentioning
confidence: 99%
“…MAC may act as a direct source of emboli or merely as a marker of conditions associated with thrombo-embolism, such as hypertension, general atherosclerosis, advanced age, congestive heart failure, atrial fibrillation and diabetes [1-3, [16][17][18][19][20][21]. Case reports and epidemiological studies suggest a strong relation between MAC and stroke [3, [22][23][24][25][26][27][28].…”
mentioning
confidence: 99%
“…Moreover it can mimick tumors, vegetations or thrombi. Our primary concern about following the patient conservatively was increased risk of stroke [8]. Harpaz et al [9] followed 13 patients with mitral annular calcification and caseous necrosis conservatively over 3.8 years and stroke occured in none of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated an association between stroke and mitral annular calcification (MAC), although a causal link has not been established. 10 The mechanism of stroke is thought to be embolic, and thrombus overlying MAC has been described, 10 but calcific embolism has also been suggested. 1 We presume thromboembolism was the mechanism of the transient ischaemic attack.…”
Section: Discussionmentioning
confidence: 99%